PENGEMBANGAN MODUL PEMBELAJARAN PERBAIKAN PERALATAN LISTRIK KELAS XII TITL DI SMK NEGERI 14 MEDAN - Bangun, Angga Karisto; Pangaribuan, Wanapri (JEVTE Journal of Electrical Vocational Teacher Education, 2023)
Abstract This research aims to: (1) Find out how to develop a Class XII Electrical Equipment Repair Learning Module at SMK Negeri 14 Medan. (2) Knowing the response of users of the Class XII Electrical Equipment Repair Learning Module at SMK Negeri 14 Medan. (3) Determine the level of feasibility and effectiveness of the Class XII Electrical Equipment Repair Learning Module at SMK Negeri 14 Medan. This research will be tested involving class This type of research is Research and Development (R & D) with the ADDIE research model. The ADDIE research model includes 5 stages, namely first analysis which includes analysis of product needs, second design namely compiling modules, layouts and module materials, third development namely developing products that have been designed for validation in order to get input from media experts and material experts, fourth implementation namely implementing the product to get responses from users (students) to the modules that have been developed, the fifth evaluation is evaluating the module based on several inputs from experts and user responses. The instruments used in this research were a validation questionnaire and a user response questionnaire. The results of this research are known: (1) This research development produced a product in the form of a learning module for Electrical Equipment Repair Class XII TITL at SMK Negeri 14 Medan. (2) The results of product user (student) responses in the "Very Good" category obtained an average percentage score of 93.5%. So the electrical equipment repair learning module that was developed was declared suitable for use. (3) The feasibility of this module was obtained from the validation results of media experts in the "Very Feasible" category which had a score percentage of 90%, and the subsequent validation results were obtained from material experts in the "Very Feasible" category. ” which obtained a score percentage of 88.75%. The effectiveness of the module developed in the "Very Effective" category has a score percentage of 86%. The recommendation in this research is that module development be carried out again in other subjects so that it can increase students' motivation and enthusiasm for learning. Key Words: Learning Module, Electrical Equipment Repair AbstrakPenelitian ini bertujuan untuk: (1) Mengetahui cara mengembangkan Modul Pembelajaran Perbaikan Peralatan Listrik Kelas XII di SMK Negeri 14 Medan. (2) Mengetahui respon pengguna Modul Pembelajaran Perbaikan Peralatan Listrik Kelas XII di SMK Negeri 14 Medan. (3) Mengetahui tingkat kelayakan dan efektivitas Modul Pembelajaran Perbaikan Peralatan Listrik Kelas XII di SMK Negeri 14 Medan. Penelitian ini akan diuji coba dengan melibatkan siswa kelas XII Teknik Instalasi Tenaga Listrik SMK Negeri 14 Medan semester ganjil tahun ajaran 2022/2023. Jenis penelitian ini adalah Research and Development (R & D) dengan model penelitian ADDIE. Model penelitian ADDIE meliputi 5 tahapan yaitu pertama analysis yang meliputi analisis kebutuhan produk, kedua design yaitu menyusun modul, layout dan materi modul, ketiga development yaitu mengembangkan produk yang sudah didesain untuk dilakukan validasi agar mendapatkan masukan oleh ahli media dan ahli materi, keempat implementation yaitu menerapkan produk untuk mendapatkan respon dari pengguna (siswa) terhadap modul yang telah dikembangkan, kelima evaluation yaitu mengevaluasi modul berdasarkan beberapa masukkan dari para ahli serta respon pengguna. Instrumen yang digunakan pada penelitian ini adalah angket validasi dan angket respon pengguna. Hasil Penelitian ini diketahui : (1) Penelitian pengembangan ini menghasilkan produk berupa modul pembelajaran Perbaikan Peralatan Listrik Kelas XII TITL di SMK Negeri 14 Medan. (2) Hasil respon pengguna produk (siswa) dengan kategori “Sangat Baik” memperoleh rata – rata presentase skor  93,5%. Maka modul pembelajaran perbaikan peralatan listrik yang dikembangkan dinyatakan layak untuk digunakan (3) Kelayakan modul ini didapatkan dari hasil validasi ahli media dengan kategori “Sangat Layak” yang memiliki presentase skor 90%, dan hasil validasi berikutnya didapatkan dari ahli materi dengan kategori “Sangat Layak” yang memperoleh presentase skor 88,75%. Efektivitas modul yang dikembangkan dengan kategori “Sangat Efektif” memiliki presentase skor 86%. Rekomendasi pada penelitian ini adalah pengembangan modul dilakukan lagi pada mata pelajaran lainnya sehingga dapat meningkatkan motivasi dan semangat belajar siswa.Kata kunci : Modul Pembelajaran, Perbaikan Peralatan Listrik